Audit committees' involvement and the effects of quality in the internal audit function on corporate governance. Issue 3 (10th July 2018) - Abdullah, Razimah; Ismail, Zubaidah; Smith, Malcolm
Abstract : Extant literature has investigated extensively the structure of the internal audit functions and the structure of audit committees and their associations with internal audit quality and the effectiveness of internal audit functions. However, few studies have investigated the activities and processes involved in internal audits. This study goes beyond the "black box" approach to investigate an audit committee's involvement in the four stages of the internal audit performance—planning, execution, reporting, and monitoring—and its corresponding impact on internal audit performance quality. In this study, data were collected by questionnaires sent to the chief internal auditors of Malaysian public listed companies. The study establishes the link between internal audit quality to corporate governance by relating internal audit quality to the number and nature of recommendations made by the internal audit teams to improve on the various dimensions of corporate governance as identified by the World Bank's corporate governance framework. The results indicate that high performance in internal auditing is associated with more recommendations to improve corporate governance dimensions. The results also suggest that specific reviews by the audit committees on internal audit activities affect audit quality or overall internal audit performance and in the quality of various stages of internal audit, particularly audit planning.